2022
DOI: 10.1002/etc.5476
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Time‐Dependent Aquatic Toxicity of Hydrocarbons: Role of Organism Weight, Temperature, and Substance Hydrophobicity

Abstract: Oil spill exposures are highly dynamic and are not comparable to laboratory exposures used in standard toxicity tests. Toxicokinetic-toxicodynamic (TKTD) models allow translation of effects observed in the laboratory to the field. To improve TKTD model calibration, new and previously published data from 148 tests were analyzed to estimate rates characterizing the time course of toxicity for 10 fish and 42 invertebrate species across 37 hydrocarbons. A key parameter in the TKTD model is the first-order rate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…These results with whole‐oil exposure suggested that the single PAC results of our study also apply to complex PAC mixtures (Scovil et al, 2023), but our results highlight that not all PACs exhibit a predictable change in toxicity with temperature. We did find that PACs with higher log K OW values (>4) were more likely to exhibit an effect at higher test temperatures, while differences in toxicity between temperatures for lower log K OW (<4) PACs were apparent in the short term (e.g., 3–12 h of exposure), which was generally resolved within 48 h, as was also observed in Redman et al (2022). The temperatures tested in Scovil et al (2023) and the present study are within the optimal range of larval lobster performance described by Quinn (2017) of 8 to 20 °C, and it is probable that at temperatures outside this optimal range, but within the critical temperature limits (4 and 26 °C), there may be other physiological processes that could exacerbate exposure to PACs (Quinn, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results with whole‐oil exposure suggested that the single PAC results of our study also apply to complex PAC mixtures (Scovil et al, 2023), but our results highlight that not all PACs exhibit a predictable change in toxicity with temperature. We did find that PACs with higher log K OW values (>4) were more likely to exhibit an effect at higher test temperatures, while differences in toxicity between temperatures for lower log K OW (<4) PACs were apparent in the short term (e.g., 3–12 h of exposure), which was generally resolved within 48 h, as was also observed in Redman et al (2022). The temperatures tested in Scovil et al (2023) and the present study are within the optimal range of larval lobster performance described by Quinn (2017) of 8 to 20 °C, and it is probable that at temperatures outside this optimal range, but within the critical temperature limits (4 and 26 °C), there may be other physiological processes that could exacerbate exposure to PACs (Quinn, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, with the phenanthrene, exposure effects were first observed at the higher temperature after 2.25 h of exposure, whereas it took 24 h of exposure (note that there were no assessments between 4.25 and 24 h) for the responses at the two temperatures to become equal. Redman et al (2022) concluded that temperature has only a minor influence on modulating toxicity, specifically on the elimination rate, but there can be differences in the rate at which effects are observable in the short term (Redman et al, 2022). A study with a conventional heavy crude oil found that larval American lobster exposed for 24 h to the highest dilution of WAF at 15 °C exhibited significantly more mortality than those exposed at 12 and 9 °C (Scovil et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger body weight implies a longer time needed before a critical oil mass has partitioned into the cell membranes to reach the CBR and produce narcotic effects. Still, in a recent modeling study, only a limited influence of body weight (or size) on the final hydrocarbon concentrations in organisms was found; however, it should be noted that this conclusion was drawn based on pooled data from different literature sources (Redman et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…A toxic effect level is reached when internal concentrations exceed the CBR. In the case of a general acutely toxic, narcotic effect, the concentration of organic contaminants within the lipid bilayer of the cell membranes of an organism exceeds a certain molar threshold concentration (Redman et al, 2022; van Wezel & Opperhuizen, 1995). Petroleum hydrocarbons generally exert such a nonpolar narcotic mode of action (De Laender et al, 2011).…”
Section: Discussionmentioning
confidence: 99%